Clinical experience with pemigatinib for previously treated metastatic cholangiocarcinoma: practical considerations from clinical cases - Jonathan Wadsley; Alan Christie; Roopinder Gillmore; Amy Trinh; Rachel Greig (BioExcel Publishing Ltd, 2023)
The management of advanced cholangiocarcinoma (CCA) is challenging. In patients with advanced CCA, gemcitabine/cisplatin combination is the standard frontline chemotherapy, with 5-fluorouracil-based regimens preserved for subsequent lines; however, the expected survival is poor. Pemigatinib was approved for locally advanced or metastatic CCA with FGFR2 fusions or rearrangement. Pemigatinib has a manageable safety profile and achieves a durable response. Nearly 50 patients with CCA have been treated with pemigatinib in the United Kingdom. However, clinical experience with pemigatinib is lacking. We present our experience with three clinical cases to illustrate the position of pemigatinib in the management of CCA and related toxicities.